The role of prayer in Shakespeare's plays - Bates, Lauren Catherine (Department of Religious Studies, 2017)
There has been a turn to religion in Shakespeare Studies by scholars like Kastan, Swift and Shugar in recent years, and this turn has uncovered a wealth of insight that had previously been obscured. I contribute to this recovery of the spiritual dimension of Shakespeare's work by tackling the question of what prayer does in his plays. I place these performed prayers in their historical and theological contexts, as well as analyse their roles dramatically and thematically within the plays. Prayer as a dramatic form is unique in that it falls between a dialogue and a monologue, pointing to something different in terms of rhetoric and content. Characters evoke an invisible being to whom they bare their souls, and the audience is privy to this conversation but not addressed by it. Awareness is created of something other, something beyond, filling the space of the stage with the suggestion of an alternate reality, another terrain beyond the earthly realm. Prayer is a conduit between characters and this alternate reality, a conduit through which multiple human impulses are conducted. I focus specifically on how filial attachment, erotic desire, violence, and visions of citizenship are conducted via prayer, and what happens when any of these impulses and visions is misdirected. Through the ability of prayer to conduct this array of human impulses, I demonstrate Shakespeare's complex engagement with the metaphysical realm, especially as his plays dramatize characters' move to embrace the divine.